Circular RNA circLDLR facilitates cancer progression by altering the miR-30a-3p/SOAT1 axis in colorectal cancer - Ruoqin Wang; Jiayu Wang; Yanjun Chen; Yuqi Chen; Qinhua Xi; Linqing Sun; Xueguang Zhang; Guangbo Zhang; Xianglin Ding; Tongguo Shi; Weichang Chen (Cell Death Discovery, 2022)
Abstract Colorectal cancer (CRC) is the third most common malignancy worldwide. Circular RNAs (circRNAs) have been reported to play critical regulatory roles in tumorigenesis, serving as tumor biomarkers and therapeutic targets. However, the contributions of circRNAs to CRC tumorigenesis are unclear. In our study, high expression of circLDLR was found in CRC tissues and cells and was closely associated with the malignant progression and poor prognosis of CRC patients. We demonstrated that circLDLR boosts growth and metastasis of CRC cells in vitro and in vivo, and modulates cholesterol levels in vitro. Mechanistically, we showed that circLDLR competitively binds to miR-30a-3p and prevents it from reducing the SOAT1 level, facilitating the malignant progression of CRC. In sum, our findings illustrate that circLDLR participates in CRC tumorigenesis and metastasis via the miR-30a-3p/SOAT1 axis, serving as a potential biomarker and therapeutic target in CRC.